Reviews and notices - Aijmer, Karin; Bowen, Rhonwen; Donovan, Stephen; Malm, Monica; Paul, Ronald; Packalén, Sture; Neuhaus, Stefan; Dentler, Sigrid; Freund, Folke; Sundqvist, Birger; Rosengren, Per; Rossiello, Leonardo (Moderna Språk, 1997)
Includes the following reviews: pp. 229-230. Karin Aijmer. Wales, K., Personal Pronouns in Present-Day English. pp. 230-231. Rhonwen Bowen. Kuiper, K. & Scott Allan, W., An Introduction to English Language. pp. 231-233. Stephen Donovan. Eagleton, T., The Illusions of Postmodernism. p. 233. Monica Malm. Krontiris, T., Oppositional Voices : Women as Writers and Translators of Literature. p. 234. Ronald Paul. Haywood, I. (ed.), The Literature of Struggle: an anthology of Chartist Literature. p. 235. Sture Packalén. Schmidt, J., Quellenlexikon zur deutschen Literaturgeschichte. p. 236. Stefan Neuhaus. Loest, E., Als wir in den Westen kamen. pp. 236-238. Sigrid Dentler. Önnefors, O., Verb-erst-Deklarativsätze. pp. 238-239. Folke Freund, Birger Sundqvist. Freund, F. & Sundqvist, B., Zur Rezension von "Tysk gymnasiegrammatik". pp. 239-240. Per Rosengren, Leonardo Rossiello. Foster, D.W., Literatura española: una antalogía.